A web of things to reduce energy wastage - Lanthaler, M.; Guetl, Christian (IEEE, 2012)
Western Australia’s economy is largely driven by the extraction and processing industry. Caused by inhospitable climate and living conditions in the remote regions, where the vast majority of the natural resources are found, housing needs for personnel are both difficult and costly to meet. The provision of energy accounts for a big part of this since it often requires the transportation of large quantities of fuel over long distances. This would suggest a responsible and effective use of energy, but often the opposite is the case. Excessive wastage is more the rule than the exception. This results not only in high costs but also considerable greenhouse gas emissions. To address these issues, we present a distributed system which drastically reduces the amount of energy wastage without affecting the quality of living of the residents. By building the system to form a Web of Things we try to simplify its management, assure its scalability, and hope to foster its use in unanticipated ways.